Vloga prsti v ekosistemu - Vovk Korže, Ana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
In 1992 the United Nations Commission for development and the World Conference for development have emphasized the significance of permanent development. It should base on the presumption, that the satisfaction of present needs do not jeopardize the needs of future generations. Considering the nature sources and the environment, it means that the environment has limited selfcleaning capacities. From the soil point of view, the permanent development means renewal and protection of all soil functions in ecosystem; in natural as well as in anthropogenic environment. The damages in soils are irreversible, that is why the permanent attitude is necessary.
Keywords: naravni viri; prst (pedologija); tla; izkoriščanje; degradacija; preprečevanje; trajnostni razvoj; sustainable development; ekosistemi; pokrajine; kulturna krajina